2014
DOI: 10.1371/journal.pone.0106640
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of a Preoperative Axillary Ultrasound and Fine-Needle Aspiration Cytology to Detect Patients with Extensive Axillary Lymph Node Involvement

Abstract: BackgroundRecent studies have demonstrated that axillary lymph node dissection (ALND) does not affect patient survival, even in those with one or two positive sentinel lymph nodes (SLNs). On the other hand, patients with 3 or more metastatic lymph nodes are eligible for chemotherapy. Therefore, it is crucial to identify a priori patients at risk of having a high number of metastatic axillary lymph nodes for their surgical and/or clinical management. Ultrasound (US) guided Fine-Needle Aspiration (FNA) has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
1
14
0
1
Order By: Relevance
“…AFNA is a simple, inexpensive, and minimally invasive technique that makes possible reduction in the numbers of SN biopsies performed [19] [20]. Previous studies have reported that the sensitivity of AFNA was low and the false-negative rate was high [7] [10] [19] [20]. In this study, all patients with AFNA+ findings had metastatic disease at ALND.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…AFNA is a simple, inexpensive, and minimally invasive technique that makes possible reduction in the numbers of SN biopsies performed [19] [20]. Previous studies have reported that the sensitivity of AFNA was low and the false-negative rate was high [7] [10] [19] [20]. In this study, all patients with AFNA+ findings had metastatic disease at ALND.…”
Section: Discussionmentioning
confidence: 68%
“…Although LNM ≥ 4 should be considered for RNI [7], propriety is unknown regarding ALND omission. The omission of ALND in surgical procedures for tumors with LNM has been considered, but remains controversial [8].…”
Section: Discussionmentioning
confidence: 99%
“…This preference does not apply for sampling of lymph nodes suspected to be metastatic at ultrasound of axilla, where fine needle aspiration has been shown to be effective [34]. …”
Section: Preference For Core or Vacuum-assisted Biopsymentioning
confidence: 99%
“…Several studies have found AUS and USG-FNAC useful in the preoperative work-up of BC patients [9-11], but AUS characteristics such as lymph node size, cortical morphology, contour, and hilar fat were not individually predictive of final cytology and pathology [12]. …”
Section: Introductionmentioning
confidence: 99%